2021
DOI: 10.3390/antibiotics10040410
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Antibiotic Residues and Antibiotic Resistant Bacteria in Cattle Manure Intended for Fertilization of Agricultural Fields: A One Health Perspective

Abstract: Antibiotic resistant bacteria and antibiotic residues can enter the environment when using animal manure as fertilizer. Twenty-five mixed beef cattle farmyard manure samples and 9 mixed fattening calf slurry samples from different farms across Belgium were investigated for the presence of 69 antibiotic residues, antibiotic resistant Escherichia coli and Salmonella spp. Doxycycline, oxytetracycline, ciprofloxacin, enrofloxacin, flumequine and lincomycin were detected in all fattening calf slurry samples with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…Quinolones have been reported to be persistent in manure with dissipation time (DT 90 ) ranging from 100 to 5800 days (Berendsen et al 2018 ). In a recent study, nalidixic acid–resistant E. coli was found in beef cattle farmyard manure, which contributed to 1.2% of the total resistant isolates (Huygens et al 2021 ). In the current study, the cultivable bacteria present in the manure samples showed significant resistance (22%) against nalidixic acid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quinolones have been reported to be persistent in manure with dissipation time (DT 90 ) ranging from 100 to 5800 days (Berendsen et al 2018 ). In a recent study, nalidixic acid–resistant E. coli was found in beef cattle farmyard manure, which contributed to 1.2% of the total resistant isolates (Huygens et al 2021 ). In the current study, the cultivable bacteria present in the manure samples showed significant resistance (22%) against nalidixic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the total AMR recorded in manure samples, ampicillin and sulfadiazine resistance contributed to 14% and 13%, respectively. Sulfonamides are widely present in human and animal wastes (Adekanmbi et al 2020 ; Huygens et al 2021 ). A recent study reported that 75% of sulfonamide-resistant bacteria were found to be resistant to ampicillin (Adekanmbi et al 2020 ), which is in accordance with the data obtained in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the resistance of telluric communities to invasion can be enhanced after a rst invasion [20]. Another factor that can modulate invasion events in autochthonous microbiota refers to the possible presence of antibiotics in manure, which is frequently reported in the literature [21,22]. These contaminants may disturb interaction patterns of microbial communities according to the antibiotic sensitivity pro le of their respective members [23,24], thus favoring the emergence of communities that would differ from those obtained under antibiotic-free environments.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, wild or domestic animals, animal production, and animal-based agricultural systems are linked to the spread of AMR to humans and the environment [ 13 ]. The excessive or inadequate use of antibiotics in animal farming drives AMR [ 14 ] by favouring the increase in the number of resistant strains in farm animals, animal origin-food, and animal manure [ 15 , 16 ]. AMR bacteria in animal-origin food may cause foodborne-disease outbreaks, remain as commensals, and bring about drug-resistant infections later [ 17 ].…”
Section: Introductionmentioning
confidence: 99%